2012
DOI: 10.1002/ange.201200669
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Bifunctionality of Bacterial Phenylalanine Aminomutase and Ammonia Lyase Enzymes

Abstract: Enzymatischer Thermoschalter: Die bakteriellen 4‐Methylidenimidazol‐5‐on‐abhängigen Enzyme AdmH und EncP zeigen bemerkenswerte thermische Bifunktionalität: Bei niedriger Temperatur agieren sie als Mutasen (blauer Graph) und bei höheren Temperaturen hauptsächlich als Lyasen (roter Graph). Dieser temperaturabhängige Wechsel der Enzymklasse erklärt auch, warum diese ähnlichen Enzyme unterschiedliche katalytische Funktionen im sekundären Metabolismus wahrnehmen können.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…Strikingly, both enzymes were found to exhibit mutase activity at lower temperatures with only minimal production of cinnamate when L-phenylalanine was used as a starting material. 193 This finding was in accordance with the leaking of cinnamate reported upon the first biochemical characterization of AdmH 187 and also explains in part the apparently low reaction rate for EncP in initial studies, 192 where only formation of the ammonia-lyase product cinnamate was measured. At higher temperatures, both enzymes were seen to produce an increasing amount of cinnamate, with minimal PAM activity detectable at temperatures of around 70 °C (Scheme 15).…”
Section: Chemical Reviewssupporting
confidence: 87%
See 2 more Smart Citations
“…Strikingly, both enzymes were found to exhibit mutase activity at lower temperatures with only minimal production of cinnamate when L-phenylalanine was used as a starting material. 193 This finding was in accordance with the leaking of cinnamate reported upon the first biochemical characterization of AdmH 187 and also explains in part the apparently low reaction rate for EncP in initial studies, 192 where only formation of the ammonia-lyase product cinnamate was measured. At higher temperatures, both enzymes were seen to produce an increasing amount of cinnamate, with minimal PAM activity detectable at temperatures of around 70 °C (Scheme 15).…”
Section: Chemical Reviewssupporting
confidence: 87%
“…While at lower temperatures the inner active site loop would remain in the closed conformation long enough for deamination and reamination to occur, at higher temperatures interruption of the catalytic cycle (with loop opening and release of the intermediate) would result in ammonia-lyase activity. 193 From a physiological perspective, knowledge of the distinct pathways associated with EncP and AdmH allows speculation that, while both enzymes possess unwanted side activities, they are unlikely to have detrimental wasteful effects in vivo. This is because AdmH has been shown on two accounts to produce only a small amount of unproductive cinnamate 187 and EncP, while able to form a sizable amount of (S)-β-phenylalanine, can also revert it to metabolically active L-phenylalanine or deaminate it to cinnamate 193 under the same conditions.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential stimulated reaction is mild and can be easily operated, 18−22 which opens up new possibilities for many biocatalysis systems that are sensitive to change of temperature and acid base reagents. 28 The host polymer 8A PEG-CD was obtained from the click reaction of 8A PEG with alkyl end groups and β-CD modified with azide groups (Scheme S1), whereas the guest polymer 8A PEG-Fc was synthesized by the esterification between 8A PEG and ferrocenecarboxylic acid (Scheme S2). Their structures were characterized by 1 H NMR and FT-IR (Figure S1−S2).…”
mentioning
confidence: 99%
“…5,29−31 One study showed how increasing the reaction temperature promoted ammonia lyase activity catalyzed by PaPAM isolated from Pantoea agglomerans. 31 A separate study switched a PAM to a PAL by mutating four residues (Leu97, Ala77, Ile79, and Cys89) of the inner loop structure of Taxus chinensis (TchPAM) [essentially identical (97%) in sequence to TcPAM from T. canadensis] to those in PcPAL (Gly127, Thr107, Ser109, and Thr119, respectively). 30 The sequence of the same loop region of OsTAM is 54% identical to that in TcPAM and 66% identical to that in PcPAL than in TcPAM.…”
Section: ■ Results and Discussionmentioning
confidence: 99%